Audubon : The Kentucky Years - Keating, L. Clark (Louis Clark), 1907-1991 (Book collections on Project MUSE., 2009)
Kentucky attracted an amazing variety of would-be settlers in pioneer days, but none with brighter talent than John James Audubon. Although his years in the state came long before publication of the monumental Birds of America, he was already painting the scenes from nature that were to make him famous. Audubon: The Kentucky Years is the captivating account of Audubon's sojourn in Kentucky from his arrival in in 1807 as a gregarious twenty-two-year-old storekeeper to his departure in 1819, when his failure in business was about to force him to seek a livelihood from his skill as an artist.